The effect of mild-to-moderate hearing loss on auditory and emotion processing networks - Husain, Fatima T.; Carpenter-Thompson, Jake R.; Schmidt, Sara A. (Frontiers in Systems Neuroscience, 2014)
We investigated the impact of hearing loss on emotional processing using task- and rest-based functional magnetic resonance imaging. Two age-matched groups of middle-aged participants were recruited: one with bilateral high-frequency hearing loss (HL) and a control group with normal hearing (NH). During the task-based portion of the experiment, participants were instructed to rate affective stimuli from the International Affective Digital Sounds database as pleasant, unpleasant, or neutral. In the resting state experiment, participants were told to fixate on a '+' sign on a screen for five minutes. The results of both the task-based and resting state studies suggest that NH and HL patients differ in their emotional response. Specifically, in the task-based study, we found slower response to affective but not neutral sounds by the HL group compared to the NH group. This was reflected in the brain activation patterns, with the NH group employing the expected limbic and auditory regions including the left amygdala, left parahippocampus, right middle temporal gyrus and left superior temporal gyrus to a greater extent in processing affective stimuli when compared to the HL group. In the resting state study, we observed no significant differences in connectivity of the auditory network between the groups. In the dorsal attention network, HL patients exhibited decreased connectivity between seed regions and left insula and left postcentral gyrus compared to controls. The default mode network was also altered, showing increased connectivity between seeds and left middle frontal gyrus in the HL group. Further targeted analysis revealed increased intrinsic connectivity between the right middle temporal gyrus and the right precentral gyrus. The results from both studies suggest neuronal reorganization as a consequence of hearing loss, most notably in networks responding to emotional sounds.